re-expression inhibits growth and enhances radiosensitivity in nasopharyngeal carcinoma - Mei Tang; Ru-yan Liu; Cong Zhou; Meng-zhen Yuan; Dong-ming Wu; Zhu Yuan; Peng Zhang; Jin-yi Lang (Tumor Biology, 2017)
Although radiation therapy is the primary treatment for nasopharyngeal carcinoma, radioresistance remains a major obstacle to successful treatment in many cases, and the exact underlying molecular mechanisms are still ill-defined. EMP2 , epithelial membrane protein-2, was a recently identified potential oncogene involved in multiple biological processes including cell migration and cell proliferation. This study was to explore the potential relationship between EMP2 expression, nasopharyngeal carcinoma genesis, and radioresistance. EMP2 expression status in 98 nasopharyngeal carcinoma clinical samples was examined by immunohistochemical staining. As a result, most of the nasopharyngeal carcinoma tumor samples were weakly or negatively stained, while paired adjacent normal tissues were moderately or strongly stained. Moreover, patients with higher expression of EMP2 had significant longer survival times. EMP2 re-expression suppresses cell growth, induces S-phase cell cycle arrest, and promotes radiosensitivity and apoptosis in nasopharyngeal carcinoma cells. These results support that loss of EMP2 is common, and its re-expression may serve as an approach to enhance radiation sensitivity in nasopharyngeal carcinoma.